Gastrointestinal Complications Depending on the Selectivity of Non-Steroidal Anti-Inflammatory Drug - G.V. Dzyak; Yu.M. Stepanov; I.V. Kushnirenko (Gastroenterologìa, 2013)
The article deals with the problem of gastrointestinal complications during administration of nonsteroidal anti-inflammatory drugs, commonly used to treat a range of conditions, particularly rheumatic diseases. The results of own researches, which served to define the characteristics of changes in the state of gastric secretory function in patients receiving non-selective and selective anti-inflammatory agent and their comparative analysis, are provided. The data obtained demonstrated a certain contribution to the understanding of the mechanism of development of complications from the gastrointestinal tract when taken drugs of above group.